The capture - Lasky, Kathryn (New York : Scholastic, 2003)
A classic hero mythology about the fight between good and evil, Guardians of Ga'Hoole is filled with adventure, suspense, and heart.Soren is born in the forest of Tyto, a tranquil kingdom where the Barn Owls dwell. But evil lurks in the owl world, evil that threatens to shatter Tyto's peace and change the course of Soren's life forever.Soren is captured and taken to a dark and forbidding canyon. It's called an orphanage, but Soren believes it's something far worse. He and his friend Gylfie know that the only way out is up. To escape,...
R
730
R
Keywords: Owls -- Juvenile fiction; Gylfie (Fictitious character) -- Juvenile fiction; Tyto (Imaginary place) -- Juvenile fiction